Intellectual capital and property tax reassessment performance of local authorities: The interrelationships analysis - Senawi, Asma; Osmadi, Atasya (Frontiers in Psychology, 2022)
Malaysia’s property tax reassessment practices have recently revealed a previously hidden phenomenon that insufficient numbers of local authorities had undertaken a revaluation. The situation raises the question of what causes variations in property tax reassessment performance and which factors contribute to these variations. Hence, this study investigates the role of intellectual capital (IC) and its components in property tax reassessment performance among Malaysian local authorities. The interrelationships between these components are also examined. The study used quantitative research methods. Data were collected using structured questionnaires from a sample of 155 officers from local authorities operating in West Malaysia. Structural equation modelling (SEM) was employed to examine the hypotheses using the SmartPLS 4.0.8.2 version of the partial least squares technique. The analysis results demonstrate that only relational capital significantly affects property tax reassessment performance, whereas human and structural capital have no equivalent relationship. Intriguingly, significant interrelationships were observed among the components of IC. The research model adds theoretical value to the discourse of organizational psychology, knowledge management, and property tax reassessment management. The significant positive relationship on relational capital resulting from this research indicates that the multiple stakeholder’s behaviours impacted reassessment work. The study addressed the vital part of the literature gap by considering the aspect of intellectual capital among local authorities in conducting property tax reassessment. This study offers practical managerial implications for the related parties: local authorities, public institutions and other stakeholders. The findings will change the manager’s behaviour in realizing the importance of IC and making effective strategies to improve their property tax reassessment performance.